Conjunctival bacterial flora in diabetic patients (Ibrahim Medical College Journal, 2014)
Conjunctival flora refers to population of microorganisms that dwell within the eyes of healthy individuals and is important in maintaining a healthy ocular surface and normal conjunctival function. Conjunctival flora may be altered by a variety of factors that include age, immunosuppression and geography. Immune function is compromised in diabetes mellitus. The aim of the present study was to see the pattern of conjunctival bacterial flora in diabetic and non-diabetic patients. This cross sectional study was carried out in BSMMU during the period of January 2011 to December 2011. Total 500 conjunctival swabs were collected from both eyes of 50 diabetic patients attending OPD of Endocrinology Department of BSMMU and 200 non-diabetic individuals. Significant number of culture was positive in diabetic patients (64.0%) compared to that of non-diabetic individuals (38.0%). Staphylococcus epidermidis was predominant in both study groups (diabetic vs non-diabetic: 41.3% vs 65.26%). Staphylococcus aureus (15.22%), Escherichia coli (6.52%) and Enterobacter (8.33%) were isolated in diabetic patients. Rate of positive culture in both and single eyes were higher in diabetic (28%, 36.0%) than that of non-diabetic individuals (9.5%, 28.5%). DOI: http://dx.doi.org/10.3329/imcj.v7i1.17698 Ibrahim Med. Coll. J. 2013; 7(1): 5-8